Effect of Initial Spacing on Production of Pulpwood in Pinus tecunumanii - Torvi, R. K.; Kariyappa, G. S.; Satishchandra, K. M. (Indian Forester, 1998)
To determine the optimum spacing that gives maximum production of high est quality pulpwood in the shortest time, a spacing trial was established in Pinus tecunumanii during 1988 using 1 m × 1 m, 2 m × 2 m, 2.5 m × 2.5 m, 3 m × 3 m, 3.5 m × 3.5 m, 4 m × 4 m and 5 m × 5 m spacings. Data collected upto end of 8th year are presented in this paper. Analysis of data indicated that height was not affected by different spacing while Diameter at Breast Height (DBH) was highest at widest spacing and lowest at closest spacing. Further, Height to DBH ratio decreased with increase in spacing indicating a lower Form-Factor at wider spacing. Total Stand Volume per hectare and Mean Annual Volume Increment (Mal) were highest in 1 m × 1 m spacing and decreased with increase in spacing. In 1 m × 1 m spacing there is intense competition between trees which resulted in high mortality and thin trees producing small quantity of pulpwood whose extraction is expensive and uneconomical. In other spacings, trees are distributed in diameter classes that produce pulpwood of desirable size. Considering volume production and distribution of trees in different diameter classes, maximum production of pulpwood is anticipated at 2.5 m × 2.5 m spacing which gives a planting density of 1,600 plants per ha at the rotation period of 12 years.